KEDAULATAN, TERITORIALITAS, DAN KEAMANAN PASCA WESTPHALIA - Anggoro, Kusnanto (Global: Jurnal Politik Internasional, 2004)
There are real technological and normative changes that have strengthened the need to reconceptualize the concepts of statehood, security, and sovereignty. The sources of sovereignty, internal legitimacy, and external recognition, have been in serious flux. More than ever before, power or authority had been defined along functional, not territorial lines. The individual right to security of person entails an obligation on the part of the state to implement this right and that individual right to security of state entails an obligation the part of international community to implement this right. Norms are getting more imperative in international relations. Recent development shows that coercive power is being introduced in this phenomenon. This article argues that sovereignty is nonetheless an empirical phenomenon less than a legal on and social phenomenon. A nebulous future awaits. In the absence of world government capable of asserting its legitimate claim, normative authority would confront the fortress of power demanding sort of non-compliance sovereignty. The struggle for global norms through coercive sovereignty may end up with global anarchy.